Analysis of Landslide Vulnerability in Conto Village, Bulukerto Subdistrict, Wonogiri Regency - Sanjaya, Zabilla Tomy; Puspitosari, Anggita; Hidayat, Agung (Prospect Publishing, 2023)
This study analyses the susceptibility to landslides in Conto Village, Bulukerto Subdistrict, Wonogiri Regency. Through mapping and modelling, the research identifies factors influencing landslide vulnerability. The findings reveal that Conto Village has a Moderate level of susceptibility, covering an area of 486.96 hectares or 42.93%. The northern part of the village exhibits the highest vulnerability, attributed to slopes exceeding 45 degrees. Primary factors include slope steepness and soil type. A landslide susceptibility map is generated as a pre-emptive guide to avoid vulnerable areas, while governmental efforts such as constructing slope-retaining walls are identified as preventive measures. These findings are anticipated to enhance the preparedness of the community and government in addressing landslide risks in Conto Village, providing guidance for similar regions. Through the implementation of these measures, it is expected to minimize the impact of landslide disasters and contribute to sustainable development in the area.